Covert Hinduism, Overt Secularism : A Postsecular Reading of the Indian English Novelistic Tradition - Vescovi, Alessandro (Milano University Press, 2024)
In this book, the term "postsecular" does not denote a rejection of secularism; rather, it parallels the "post" in "post-modern" or "post-structuralist." Vescovi argues that secularism has helped Indian fiction to reach an international audience but, at the same time, has forestalled the recognition of Hindu elements covertly woven into the narrative fabric of several modern Indian classics. His close reading is an attempt at tracing traditional elements, such as plot patterns, naming, ethics in otherwise secular narratives, countering the hegemony of rationalistic interpretive paradigms often employed by postcolonial criticism.